#### 1.   Expand (x + 4)(x + 2)

 First ( x )( x )  = + x2 Outer ( x )( + 2 )  = + 2x Inner ( + 4 )( x )  = + 4x Last ( + 4 )( + 2 )  = + 8

=   x2 + 2x + 4x + 8
=   x2 + 6x + 8

#### 2.   Expand (x − 4)(x − 2)

 First ( x )( x )  = + x2 Outer ( x )( − 2 )  = − 2x Inner ( − 4 )( x )  = − 4x Last ( − 4 )( − 2 )  = + 8

=   x2 − 2x − 4x + 8
=   x2 − 6x + 8

#### 3.   Expand (2x + 3)(x − 6)

 First ( 2x )( x )  = + 2x2 Outer ( 2x )( − 6 )  = − 12x Inner ( + 3 )( x )  = + 3x Last ( + 3 )( − 6 )  = −18

=   2x2 − 12x + 3x − 18
=   2x2 − 9x − 18

#### 4.   Multiply out (2x − 3)(x + 6)

 First ( 2x )( x )  = + 2x2 Outer ( 2x )( + 6 )  = + 12x Inner ( − 3 )( x )  = −3x Last ( − 3 )( + 6 )  = −18

=   2x2 + 12x − 3x − 18
=   2x2 + 9x − 18

#### 5.   Multiply out (x − 5)(3x + 3)

 First ( x )( 3x )  = + 3x2 Outer ( x )( + 3 )  = + 3x Inner ( − 5 )( 3x )  = −15x Last ( − 5 )( + 3 )  = −15

=   3x2 + 3x − 15x − 15
=   3x2 − 12x − 15

#### 6.   Multiply out (x + 5)(3x − 3)

 First ( x )( 3x )  = + 3x2 Outer ( x )( − 3 )  = − 3x Inner ( + 5 )( 3x )  = + 15x Last ( + 5 )( − 3 )  = −15

=   3x2 − 3x + 15x − 15
=   3x2 + 12x − 15

#### 7.   Remove the brackets (2x + 3)(4x + 3)

 First ( 2x )( 4x ) = + 8x2 Outer ( 2x )( + 3 ) = + 6x Inner ( + 3 )( 4x ) = + 12x Last ( + 3 )( + 3 ) = + 9

=   8x2 + 6x + 12x + 9
=   8x2 + 18x + 9

#### 8.   Remove the brackets (2x − 3)(4x − 3)

 First ( 2x )( 4x ) = + 8x2 Outer ( 2x )( − 3 ) = + 6x Inner ( − 3 )( 4x ) = −12x Last ( − 3 )( − 3 ) = + 9

=   8x2 − 6x − 12x + 9
=   8x2 − 18x + 9

back to: